Treatment of Discogenic Low Back Pain: Current Treatment Strategies and Future Options—a Literature Review - Zhao, Lei; Manchikanti, Laxmaiah; Kaye, Alan David; Abd-Elsayed, Alaa (Current pain and headache reports, 2019)
Purpose of Review Many studies have demonstrated that discogenic low back pain is the most common type of chronic low back pain (CLBP), one of the major causes of disability, and has a major socioeconomic impact. Our aim is to review present therapeutic interventions for discogenic low back pain. Recent Findings There are a multitude of treatments used in clinical practice to treat CLBP, but there is continued debate and lack of consensus among clinicians and the policy makers as to which modality is the best approach. Based on controlled evaluations, lumbar intervertebral discs have been shown to be the source of chronic back pain without disc herniation in 26 to 39% of patients. Treatment modalities include noninvasive treatments such as drug therapy, multiple physical modalities, and multidisciplinary biopsychosocial rehabilitation; interventional modalities such as intradiscal therapies and epidural injections; and regenerative modalities with disc injections of various solutions; and, finally, surgical approaches such as fusion and artificial disc replacement, all of which are accompanied by significant discussion, limited evidence, and lack of consensus. Summary The results of this evaluation show that the evidence for drug therapy in chronic discogenic low back pain is limited; for multidisciplinary biopsychosocial rehabilitation, it is moderate; and for multiple physical and behavioral therapies, the evidence is limited. For intradiscal therapies, it is poor; for epidural injections, it is moderate; and for regenerative therapies, evidence levels of 3 to 4. The evidence for surgical fusions and disc replacement is similar, without superiority when compared with multidisciplinary biopsychosocial rehabilitation, well-designed physical therapy, or epidural injections.